ECHOES OF RABELAISIAN LAUGHTER IN THE LITTLE PRIMER FOR BIG CHILDREN BY MIHAILO MAKSIMOVIĆ (Heritage, 2025)
The paper examines the beginnings of satire as a procedure in constructing a literary work on Serbian, but also on wider European soil. It primarily studies the background of satirical poetry deeply connected with the Renaissance rituals of carnivalization and the laughter of Rabelais' legacy stemming from it. It describes the beginnings of satirical genres, imbued with laughter as a philosophical and critical, and not just a physiological phenomenon, which began in our literature in the eighteenth century, with the appearance of the Little ABC Book for Big Kids by the enlightened author Mihail Maksimović. It also investigates the share of irony in the speech of the personal narrator in Maksimović's work and how irony, as a stylistic and expressive tool, establishes correlations with Bakhtin's theory of carnivalization. Also, to capture as broad a picture of the intellectual development of the Serbian rationalist man as possible, the key content determinants of Maksimović's "ABC book" are interpreted with reference to formal innovations. Finally, the paper examines its reach and influence, created as a reflex and reincarnation of the Renaissance spirit - the progenitor of critical thought.
Keywords: laughter, satire, enlightenment, Mihailo Maksimović, François Rabelais.